Introduction to International Students and COVID-19 - Widodo, Handoyo Puji; Ferdiansyah, Sandi; Fridani, Lara (Journal of International Students, 2020)
In this special edition, we address international students and COVID-19 in the higher education context. To begin with, three articles explore the sources of information used by Indonesian students interested in studying abroad, challenges faced by international students who studied in Indonesia, and the psychological well-being of Indonesian students studying in Taiwan. Although empirical studies reported in those three articles were undertaken before the prevalence of the COVID-19 pandemic, they are still relevant to this edition because they address practical implications for post-pandemic overseas studies. Other articles look into different dimensions of international students’ academic and non-academic experiences during the COVID-19 pandemic. We hope that this special edition can provide a better understanding of international students in the COVID1-19 pandemic context and beyond.